Acoustic repertoires related to surface behaviours of the Irrawaddy dolphins (Orcaella brevirostris) in Brunei Bay, Malaysia - Hairul Masrini Muhamad; Xu, X.; Zhang, X.L.; S.A. Jaaman; A.M. Muda; F.D. Haji Ismail; N. Azizul (Akademi Sains Malaysia, 2022)
Behavioural observation and acoustic recordings of Irrawaddy dolphins (Orcaella brevirostris) were performed simultaneously in Brunei Bay, Malaysia. Surface behavioural observations were classified into four categories: travelling, foraging, socialising, and milling. A total of 8.43 hours of acoustic recordings were used to retrieve four different types of sounds: whistles, burst-pulsed sounds, click trains, and biphonal sounds. The recorded whistles were frequency-modulated sounds with durations ranging from 0.06 to 3.86 s and a mean minimum frequency of 6.5±2.5 kHz. The burst-pulsed frequency ranged from >48 kHz in at least four variations. Click trains were made up of broadband clicks with variable inter-click intervals and frequencies >48 kHz. The first biphonic sounds for Irrawaddy dolphins have been revealed in this study. Whistle rates were extremely high in milling. Compared to travelling and foraging, socialising had a significantly higher rate of click trains. Across all surface behaviours, there was no significant difference in burst-pulsed rates. This study laid the groundwork for ongoing monitoring of Irrawaddy dolphins and expanding conservation efforts for this species in Malaysia